FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN AKTIVITAS OLAHRAGA PENDERITA DIABETES MELITUS - Ahmadi, Candra; Hasneli, Yesi; Woferst, Rismadefi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Sports activities or physical exercise is useful as a controlling blood sugar levels and weight loss inpeople with diabetes mellitus. This study aims to determine the factors associated with sportsactivities of people with diabetes mellitus. The design of this research is descriptive correlation andCross Sectional approach. The sample of this research was 47 respondents taken based on theinclusion criteria by using purposive sampling technique. The measuring tools used arequestionnaires that have been tested Valid and Reliabel. The analysis used is univariate analysis toknow the frequency distribution and bivariate to know the correlation (correlation) using Chi-Squaretest. The result of the research shows that there is a correlation of knowledge with sports activity ofdiabetes mellitus patient (p value 0.000 <α 0,05), no attitude relation with sport activity of diabetesmellitus patient (p value = 0.317> α 0,05) with activity of diabetes mellitus (p value = 0,114> α 0,05)and no relation of family support to sport activity of diabetes mellitus patient (p value = 0.359> α0,05). Based on this research, it is suggested to people with diabetes mellitus to be able to increasetheir knowledge about the importance of sports activity in the management of diabetes mellitus and tohealth center as health facility to provide continuous information about sport activity and to makesport activity program useful in diabetes mellitus management.Keywords: Diabetes mellitus, related factors, sports activities